IMPLEMENTATION AND IMPACT OF TEACHER CERTIFICATION PROGRAM IN INDONESIA (PERSPECTIVE IN EDUCATION) - Ramli, Ramli (Pusat Pengembangan Bahasa IAIN Tulungagung, 2014)
Education is an effort which is done by people to develop their self competence through a process of learning. Teacher certification program in Indonesia mandated by the Law Number 14, year 2005 on Teachers and Lecturers (or the so called Teachers Law) is an effort by Indonesian government to improve the quality of education in Indonesia. Certified teachers are believed to perform better than teachers who have not been certified. People assume that they have enough competencies in teaching. In fact, many teachers do not follow the process of teacher certification program fairly. There are some cases of deceit done by the teacher certification program participants. However, the finding suggests no impact of the certification on student?s performance, it may confirm some concerns that the certification?s objective is not oriented to teacher?s performance, but more to their living standard, as reflected by their student?s achievement that does not make any progress. Therefore, we need to create a better solution on how to improve the teacher certification program. Such improvement in the system can be developed by experts in greater detail but in any case, they need to have characteristics, at the fullest extent, of a performance-based system.